Application of "Hati" (Reproductive Health) Video to Increase Knowledge and Attitudes on Reproductive Health in Prospective Bride and Groom - Indah Dewi Ridawati; Kiki Sulaningsi (Syntax Literate, 2022)
The Maternal Mortality Rate in Musi Rawas has increased. This is still a serious problem because the initial rate of the strategic plan (in 2010) was 102 per 100,000 live births and the final rate during the strategic plan period (2015) was 169 per 100,000 live births. The purpose of the study was to determine the effect of the HATI video on reproductive health knowledge and attitudes in prospective brides. This research is a quasi-experimental research with pre-post without a control group. The sample used is an accidental sampling of as many as 60 people. The Wilcoxon test showed that there was a difference in the value of reproductive health knowledge and attitude (p=0.000). The conclusion there was a significant increase in reproductive health knowledge and attitudes before and after being given the video. Suggestions to KUA to be able to use the 'HATI' video as a method of promoting reproductive health.